Development of fuel additives to enhance the performances of four-cylinder spark-ignition engine / Mohd Khaizalfitri Mhd Yaakob, Mohd Azahar Mohd Ariff, Mahamad Hisyam Mahamad Basri, Sharzali Che Mat and Azmi Husin - Mohd Ariff, Mohd Azahar; Mahamad Basri, Mahamad Hisyam; Che Mat, Sharzali (Universiti Teknologi MARA, Pulau Pinang & Pusat Penerbitan Universiti (UPENA), 2013)
The increasing demand for fuel has forced the world to adapt and seek alternatives. This paper studied the most effective blend of fuel additives which can reduce fuel consumption and increase engine performance. Firstly, fuel additives used in the aftermarket were analysed using GC-MS (Gas Chromatography-Mass Spectrometry). The analysis indicated that the fuel additives chemical compositions consist of combustion improver, antiknock, deposit control, oxygenates and also fuel stabilizer. After that, new formulated blends of fuel additives were produced based on the result data obtained from the GC-MS. The dynamometer test using 4 cylinders spark ignition (SI) engine was carried out in order to compare the baseline fuel and the new formulated blends of fuel additives. It was found that the additives blend of 29.03% kerosene, 10.75% acetone, 38.71% methanol and 21.51% toluene, was proven to be the most promising. The blend helped increase engine torque performance and also reduced fuel consumption up to 13%. This finding shows a huge potential to reduce our dependency on fossil fuel.